Misinterpretation of the CT Value Assessment in the Covid 19 Test Examination with the PCR SWAB Means of Healing - Diaty Gusliani; Siti Warda; Sri Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine CT Value Knowledge in the Covid 19 Test examination with the PCR SWAB method as a measure of healing, this examination method has been carried out following government policy at the beginning of the emergence of the Covid 19 virus which was announced in Indonesia. This study used qualitative methods of observation and documentation as well as sources of secondary data which were conducted through social media including interviews with experts and community sources on YouTube digital media, journals and websites for PCR examination laboratories and hospitals. The results of this study indicate that assessing the value of CT according to government policies is universal because it originates from policies established throughout the country.